Association of Circulating Fatty Acid Profiles With Cardiovascular and All‐Cause Mortality in the General Population: A Cohort Study - Xiaogang Lv; Qianqian Ji; Qi Liu; Qingya Zhao; Yue Xu; Yaxian Meng; Liqiong Zhou; Zhao Hu; Na Wang; Yiqiang Zhan (eFood)
ABSTRACT The association between circulating fatty acids (FAs) and mortality remains unclear. This study investigates the association between circulating FA and mortality, focusing on all‐cause and cardiovascular disease (CVD) mortality. Using data from 2517 individuals (mean age 48.2 years) in the National Health and Nutrition Examination Survey (2011–2014), we analyzed FA levels and mortality using a weighted Cox proportional hazards model, with sex‐stratified analysis. In addition, restricted cubic spline was used to evaluate the FAs and all‐cause mortality on a continuous scale. Over 16,660 person‐years, 213 deaths occurred, including 73 from CVD. After multivariable adjustment, circulating saturated fatty acids (SFAs; arachidic, docosanoic, tricosanoic, and lignoceric acids) were associated with lower all‐cause mortality risk (HR per 1‐SD [95% CI]: 0.76 [0.59–0.97], 0.69 [0.56–0.85], 0.63 [0.52–0.77], 0.68 [0.59–0.80], respectively). In contrast, monounsaturated fatty acids (MUFAs; myristoleic, palmitoleic, and cis−Vaccenic acids) were associated with higher all‐cause mortality risk (HR per 1‐SD [95% CI]: 1.13 [1.04–1.23], 1.18 [1.09–1.27], 1.20 [1.09–1.32], respectively). Similar trends were observed for CVD mortality. l‐shaped nonlinear associations indicated that the lowest risk of all‐cause mortality occurred at FA concentrations between 25 and 65 μmol/L. These findings highlight the complex relationship between FAs and mortality in US adults.